Generative AI In Marketing: Productivity Gains and Work Automation - Gastman, Joel; toledobastos, Marco Bastos (AoIR Selected Papers of Internet Research, 2026)
This study explores the use of ChatGPT for social media marketing strategies and its potential impact on employment. We take stock of the literature on productivity gain and the automation of work to unpack the role of AI in devising social media marketing strategies. To this end, we carried out in-depth, semi-structured interviews with 20 social media professionals who informed a follow-up experiment using ChatGPT to generate social media marketing strategies for two companies. The results support the hypothesis of Generative AI leading to increased productivity in the creation of social media marketing, as the experiments yielded high-quality marketing strategies tailored to the specific needs of a company with consistent brand identity. The results, however, also highlight the limitations in using AI for marketing campaigns, as these tools cannot fully replicate the creativity and intuition of human professionals. We conclude with an assessment of potential risks associated with data protection and ethical considerations when using AI tools.